1993
DOI: 10.1021/ar00033a003
|View full text |Cite
|
Sign up to set email alerts
|

Expanding roles for templates in synthesis

Abstract: Watson and Crick discovered the DNA double helix in 1953 and realized immediately that its replication involved a templated synthesis.1 Their work inspired Todd to suggest in 1956 that organic templates might one day be used to control laboratory syntheses in a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
347
0
12

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 672 publications
(363 citation statements)
references
References 36 publications
4
347
0
12
Order By: Relevance
“…Using smaller molecular building blocks, an elegant templated self-assembly [203][204][205] approach yielding pure oligomeric structures of well-defined length is the Vernier principle. 206,207 Hunter has shown that two molecules, which contain a different number (n and m) of mutually complementary binding sites, separated by the same distance, interact with each other to form an assembly of accurate length (n 3 m).…”
Section: Biomimetic Templated Polymerizationmentioning
confidence: 99%
“…Using smaller molecular building blocks, an elegant templated self-assembly [203][204][205] approach yielding pure oligomeric structures of well-defined length is the Vernier principle. 206,207 Hunter has shown that two molecules, which contain a different number (n and m) of mutually complementary binding sites, separated by the same distance, interact with each other to form an assembly of accurate length (n 3 m).…”
Section: Biomimetic Templated Polymerizationmentioning
confidence: 99%
“…More recently, topological templates have become a versatile tool in peptide mimicry, and their full potential is only now about to be recognized. 10 In view of the expanding areas of applications and functions, topological templates may be generally characterized as synthetic devices, that orient functional groups or structural units in welldefined spatial arrangements. Typically, template molecules represent structural motifs such as constrained peptides, cyclodextrines, or polycyclic systems disposing selectively addressable functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical templates have an important role in the formation of complexes containing multiple components that have defined structural assemblies [1,2]. Several previous studies have shown that geometries and sizes of ligands, the coordinating ability of anions, and the nature of metals are all important in determining the structures of such complexes [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%